Evaluasi Kinerja Layanan Pengeluaran Petikemas Impor di PT. Terminal Petikemas Surabaya - Wijaya, Septyan Ade; Purwiyanto, Didik (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
PT. Terminal Petikemas Surabaya is acompany engaged in the field of services providing transportation services and loading and unloading. PT. Terminal Petikemas Surabaya is one special terminal, which serves the activities of domestic container stevedoring services, exports and imports. To make expenditures, service users must complete the documents so that the goods can be released or taken by the owner of the goods. At the time of import containers expenditures activity occurs current long build up of containers, especially at the out gate of imports, this occurs because of an error in the form of a document mismatch of container and container physical damage. To support the smooth flow of goods, then PT. Terminal Petikemas Surabaya gives procedures (ordinance) to make expenditures or import activities. In the absence of procedures then the service users do not know or will find it difficult to do a collection of goods that have been imported. Therefore, the Performance Evaluation Expenditure Service Container Import in PT. Terminal Petikemas Surabaya wich aims to improve the achievement of targets appropriate and desires of the goods (consignee), so that PT. Terminal Petikemas Surabaya can provide the best service to customers (service users).